High temperature nanoindentation response of RTM6 epoxy resin at different strain rates - Frontini, Patricia Maria (2015)
This paper explores the feasibility of characterizing the mechanical response of the commercial aerospace grade epoxy resin RTM6 by nanoindentation tests at varying temperatures and strain rates. Since glassy polymers exhibit time-dependent mechanical properties, a dynamic nanoindentation technique was used. This method consists on superimposing a small sinusoidal force oscillation on the applied force. Viscoelastic properties are then characterized by their storage and loss moduli, whereas the visco-plastic response of the material can be associated to its hardness. In such experiments, thermal stability of the measuring technique is critical to achieve a low thermal drift and it becomes increasingly important as the measuring temperature increases. Our results show that conventional methods applied for drift correction in nanoindentation of inorganic materials are not applicable to glassy polymers leading to physically inconsistent results. We propose a method for drift correction based on the hypothesis that viscoelastic modulus should be a function of the applied load and frequency but independent of the global strain rate. Using this method, it was possible to determine the viscoplastic properties of RTM6 between RT and 200 °C.